Innovative firms in emerging market countries - Amann, Edmund; Cantwell, John, 1955- (Oxford : Oxford University Press, 2012)
Based on evidence from Asia and Latin America, this book explores the role of innovative firms in emerging markets, and their contribution to growth, development, and knowledge transfer.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Business enterprises -- Asia; Business enterprises -- Latin America